Morphological and phylogenetic comparison of two myxozoan parasites infecting the gills of pikeperch (Sander lucioperca L.): Henneguya gigantea and Henneguya creplini - Graciela Colunga-Ramírez; Boglárka Sellyei; Kálmán Molnár; Csaba Székely; Gábor Cech (International Journal for Parasitology: Parasites and Wildlife)
Henneguya gigantea and Henneguya creplini have been reported as spore-forming plasmodia infecting the gills of pikeperch. However, the latter has been documented to have a broader host range. Some remarkable differences have been observed between both Henneguya species: the shape and size of plasmodia and the length of their caudal appendages. To date, no molecular evidence has been provided for H. gigantea; while for H. creplini, the 18S rDNA has been applied for its classification. In this study, we analysed morphological and molecular data to elucidate the relationship of H. gigantea and H. creplini collected from the gills of the pikeperch. Morphologically, H. gigantea resulted in a cluster of plasmodia-forming cyst bodies, while H. creplini have been mostly reported as small plasmodia. The myxospores of the two species were distinguished by the length of their caudal appendages, which were longer in H. gigantea than in H. creplini (77–100 vs 14.4–40.1 μm). The rest of the spore characters are similar in both species. The 18S and 28S rDNA sequences show low sequence distance ≤0.76 % and 0.97 %, respectively. The data presented in this study, in conjunction with those collected from previous literature, suggests that caudal appendages may exhibit phenotypic plasticity within species, which must be considered before including new members of the Henneguya genus. Furthermore, ribosomal DNA sequences serve as an essential tool for referring the taxonomic classification of myxozoans that exhibit phenotypic plasticity. We propose that H. gigantea be reclassified as H. creplini.